Participatory Ethnographic Film: Video Advocacy and Engagement with Q’eqchi’ Maya Medical Practitioners in Belize - Waldram, James B. (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2020)
There continues to be significant debate about what constitutes an “ethnographic film.” Contemporary standards for production require large budgets and sophisticated film crews, and as a result marginalizes those films produced at the local level designed to meet local needs. This article documents the process of creating a participatory ethnographic film at the behest of a group of Q’eqchi’ Maya medical practitioners in Belize. From conception through to the approval of the final cut and distribution, the project was directed by the practitioners and executed on a shoestring budget and ‘in kind’ contributions.  I argue that the genre of ethnographic film must accommodate local level aesthetic sensibilities about what constitutes a “good” representation of cultural issues, and consider the nature of the intended audience, thereby allowing space for a collaborative filmmaking process attendant to the world of the participants rather than that of international film festivals.